Utilization and development of guidance and counseling applications to support the potential development of vocational students - Mohammad Syahidul Haq; Asri Ady Bakri; Tukiyo; Al Halik; Meylia Sari (Institute of Computer Science (IOCS), 2023)
Vocational High Schools (SMK) provide technical and skill-based education, but due to a variety of factors, not all students can attain their full potential. The guidance and counseling department at SMK plays a crucial role in assisting students with the development of their potential and personal issues. However, the implementation of guidance and counseling confronts numerous obstacles, including a lack of socialization among students, ineffective counseling reports, and ineffective document storage. The objective of this study is to develop a Guidance and Counseling Information System application that incorporates information technology as a solution to problems in the implementation of guidance and counseling as a business process. The result of this study is that the system's features are tailored to user needs so that it can assist the guidance counselor in monitoring and profiling disruptive students and identifying each student's potential. The conclusion of the study indicates that the proposed features of the guidance and counseling application include reporting convenience for counselors, access for instructors, students, and parents to view counseling reports, and access to student conduct reports for principals. It is anticipated that the research will facilitate the counseling process, enhance data administration, and promote the growth of student potential